Assessing the Impact of Islamic Teachings on the Rights and Welfare of Muslim Women: A Policy and Social Justice Perspective - Houmine, Mohammed (Religion and Policy Journal, 2024)
Research Problem: The rights and responsibilities of women in Islam have often been misunderstood, particularly in the international context. Predominant narratives from Western societies frequently depict Muslim women as oppressed and lacking gender equality. This study investigates a fundamental question: has Islamic teaching contributed to the social welfare of Muslim women by granting them equitable rights and responsibilities? Research Purposes: This research aims to evaluate how Islamic teachings have influenced the social and economic well-being of Muslim women, emphasizing their rights and responsibilities. It also explores the role of religion-based policies in promoting social justice for Muslim women. Research Methods: An exploratory, inductive, and analytical approach was employed to examine Islamic teachings using primary sources, including the Qur'an and Sunnah, alongside case studies of policies and social practices affecting Muslim women’s rights. A life-cycle approach was adopted to provide a holistic view of women’s status at various stages of their lives. Results and Discussion: Findings indicate that Islam has granted significant rights and freedoms to Muslim women, such as access to education, employment, and legal protection—rights they did not enjoy prior to the revelation of the Qur'an. However, the implementation of these rights in policy and practice continues to face challenges, including social stigma and varying interpretations of religious laws. Islamic principles emphasizing social justice have demonstrably contributed to the improved welfare of Muslim women in public policy contexts. Research Implications and Contributions: This study contributes to academic discourse by exploring the intersection of religious teachings and social justice. It opens avenues for further research into how religion-based policies can be adapted to support women’s rights. These findings are particularly relevant for policymakers, activists, and scholars working on gender equality and social justice in religious contexts.